2018
DOI: 10.3389/fmed.2017.00251
|View full text |Cite
|
Sign up to set email alerts
|

Active Trachoma Cases in the Solomon Islands Have Varied Polymicrobial Community Structures but Do Not Associate with Individual Non-Chlamydial Pathogens of the Eye

Abstract: BackgroundSeveral non-chlamydial microbial pathogens are associated with clinical signs of active trachoma in trachoma-endemic communities with a low prevalence of ocular Chlamydia trachomatis (Ct) infection. In the Solomon Islands, the prevalence of Ct among children is low despite the prevalence of active trachoma being moderate. Therefore, we set out to investigate whether active trachoma was associated with a common non-chlamydial infection or with a dominant polymicrobial community dysbiosis in the Solomo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 42 publications
0
16
0
Order By: Relevance
“…This may affect the presence of other organisms in the conjunctiva. Indeed, although conflicting evidence exists, studies of human trachoma have reported that chlamydial disease is associated with a decrease in microbial richness and diversity compared to healthy controls [33,34]. Innate immune responses form a key part of the host response to chlamydial infection and, although only speculation, it is possible that upregulation of these processes at the mucosal surface may inadvertently impact on infection by other organisms such as the novel virus detected in this study [32].…”
Section: Discussionmentioning
confidence: 89%
“…This may affect the presence of other organisms in the conjunctiva. Indeed, although conflicting evidence exists, studies of human trachoma have reported that chlamydial disease is associated with a decrease in microbial richness and diversity compared to healthy controls [33,34]. Innate immune responses form a key part of the host response to chlamydial infection and, although only speculation, it is possible that upregulation of these processes at the mucosal surface may inadvertently impact on infection by other organisms such as the novel virus detected in this study [32].…”
Section: Discussionmentioning
confidence: 89%
“…A map which highlights the countries from which data were available is presented in the Supplementary Information (Supplementary Figure 2). Full details of the field and laboratory methodologies, relevant ethical and regulatory board approval are provided elsewhere 14,16,3335 . A summary of the demography of each population is provided in Supplementary Table 1, and age-specific prevalence curves for TF and sero-positivity to Ct antigens are presented in Fig.…”
Section: Methodsmentioning
confidence: 99%
“…A recent study found no association between severe scarring, classed using the FPC grading system [ 64 , 65 ], and age [ 66 ]. Seroepidemiological analyses also provided little evidence of ongoing intense transmission of infection [ 66 , 67 ]. Other pathogens ( Adenoviridae , coagulase-negative Staphylococcus , Haemophilus influenza , Moraxella catarrhalis , Staphylococcus pneumonia and Staphylococcus aureus ) were sought in these samples using PCR, but none appeared to have significant association with TF.…”
Section: Resultsmentioning
confidence: 99%
“…Other pathogens ( Adenoviridae , coagulase-negative Staphylococcus , Haemophilus influenza , Moraxella catarrhalis , Staphylococcus pneumonia and Staphylococcus aureus ) were sought in these samples using PCR, but none appeared to have significant association with TF. There was also scant evidence for conjunctival dysbiosis, a characteristic disease-associated disturbance of the microbiological community [ 67 ]. A recent analysis of gene expression in the conjunctival epithelium of Solomon Islander Ct -negative TF cases provided no evidence of an allergic aetiology [ 68 ].…”
Section: Resultsmentioning
confidence: 99%